UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN PORANG (Amorphophallus oncophyllus Prain.) TERHADAP BAKTERI Escherichia coli DAN BAKTERI Salmonella typhi - Marpaung, Jon Kenedy; Suharyanisa; Darwita Juniwati Barus; Putri (Universitas Sari Mutiara Indonesia, 2021)
Escherichia coli and Salmonella typhi are included in the pathogenic bacteria. These bacteria can cause infectious diarrheal diseases. Porang (Amorphophallus oncophyllus Prain.) leaves contain antibacterial compounds that are effective against bacterial growth. This study aims to determine the antibacterial activity of Porang leaf extract against Escherichia coli and Salmonella typhi bacteria and to determine the difference in antibacterial activity with the use of various concentrations of extracts on bacterial growth. Porang leaf extract was obtained by maceration method using 96% solvent. This test used the paper disc agar diffusion method with concentrations of 10%, 15%, 20%, and 25% against Escherichia coli and Salmonella typhi bacteria, positive control used chloramphenicol, and negative control DMSO, then tested using statistics using the ANOVA method. The results of the study on Escherichia coli bacteria obtained that the concentration and diameter of the inhibition zone with an average of three repetitions were 10% (9.41mm), 15% (11.4 mm), 20% (12.4 mm), 25% (13 .3 mm) and for Salmonella typhi, 10% (12.8 mm), 15% (13.6 mm), 20% (15.5 mm), and 20% (17.5 mm). In the positive control of chloramphenicol, the diameter of the inhibition zone was obtained with an average of three repetitions for each bacterium, namely Escherichia coli (27.5 mm) and Salmonella typhi (29.4 mm) while the DMSO negative control did not show any inhibition. The conclusion of this study showed that Porang leaf extract had activity against Escherichia coli and Salmonella typhi bacteria with strong criteria, seen from the increase in the concentration of the test solution had an increase in the diameter of the growth inhibition zone on bacteria,